Pengaruh Kompetensi, Independensi, Etika dan Pengalaman Auditor Terhadap Kualitas Audit pada Kantor Akuntan Publik di Jakarta - Raphael Kevin Hasibuan; Yoseph Agus Bagus Budi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to test the influence of Competency, Independence, Ethics and Experience of Auditors on Audit Quality at Public Accounting Firms. The type of research used in the research is quantitative with primary data sources which are data obtained directly without intermediaries by distributing questionnaires. The population of this research is Public Accounting Firms in the DKI Jakarta area. The sample was determined based on the survey method, with a total sample of 13 Public Accounting Firms (KAP) registered in the Directory of the Indonesian Institute of Public Accountants (IAPI) so that the total respondents in this study were 125 respondents. Hypothesis testing uses partial tests (t tests) and simultaneous tests (f tests). The test results prove that the results: Competence, independence, ethics, auditor experience have a positive effect on Audit Quality.